Effective Treatment in Reducing Pain in Patients With Musculoskeletal Pain Complaints - Safrin Arifin; Debrina Vita Ferezagia; Karin Amelia Safitri (Jurnal Vokasi Indonesia, 2018)
Musculoskeletal problems are complaints on the parts of the skeletal muscles felt by someone start complaints very mild to very sick. When the muscle receives static load repeatedly and for a long time will may cause complaints of damage to the joints, ligaments and tendons. Complaints to the damage this is what is usually termed the complaint musculoskeletal disorders (MSDs) or injury to the musculoskeletal system (Grandjean, 1993; Lemasters, 1996). This study aims to know a more effective treatment of electrotherapy and deep massage with massage than picking up, in reducing pain in patients with musculoskeletal pain complaints. This study used a quasi-experimental design (quasi experimental) double blind with a value of 5% negligent. This research was conducted at the Rumah Fisio Clinic and Patient’s home. These samples included 25 patients, with medical diagnosis of musculoskeletal pain who underwent physiotherapy program from May to July 2016, was taken by randomization techniques. Pain was measured by using Visual Analogue Scale (VAS). The results of the analysis of the t test showed that electrotherapy and deep massage (mean = 3.18) more effective than Picking up (mean = 2) in reducing the patient's pain..Keywords: Musculoskeletal pain , electrotheraphy , deep massage , picking up.